ToiMon: W.C. monitoring system - Alsewari, Abdulrahman A.; Saeed, Mohammed Samih; Kathir, Sharafeldin Kabashi (2021)
The size of public buildings is increasing and the number of visitors also increased as a result. The services in the public building including the toilet facilities face many issues such as lack of maintance and propper hygiene, lack of staff that could constantly follow and check the condition of each toilet. Additionally, the visitors faces some issues such as looking for the closer bathroom and knowing the availability status within a building.